A Medico Legal Study of Hanging Cases at Dhaka Medical College (Northern International Medical College Journal, 2015)
This retrospective study was conducted among 574 Autopsy cases of hanging victims at the Dhaka Medical College Morgue during the period January 2008-December 2009. Objective : The objective of this study was to find out the physical charecteristics, cause, place as well as the injuries specially in neck structures, variation of ligature materials, ligature marks, position of knot in the study subjects.Methods : A total of 5114 autopsies were performed during the study period, out of which 574(11.22%) were hanging cases. Ligature strangulation and manual strangulation cases were excluded from this study. Various Data of this hanging victims regarding places of incidence, time, suspected causes of death (related information were gathered from the victims attendants), type of suspension were noted from the inquest report accompanying the dead bodies. Points regarding ligature material, position of knot, pattern of ligature marks, injury to neck structures,fracture of hyoid bone and thyroid cartilages were collected from the 3rd copy of post mortem reports preserved in the Forensic Medicine & Toxicology Department of DMC. Finally data were analyzed and presented in table,graph and in pie chart.Results : Out of 574 hanging cases female were predominant (72.29%). Among them 304( 52.96%) were married. Marital disharmony/quarrel between couples was the main cause 172(29.96%) of hanging. Most of the victims 269(46.86%) were in the age group 21-30 years.Dopatta (orna) was the commonest 237(41.28%) ligature material. Considering the knot, most were situated at right side of neck 281 ( 48.95%).In this study single ligature mark has been found in 511(89.02%) cases and was non continuous in 478(83.27%) study subjects. In 520(90.59%) cases ligature was found above thyroid cartilage level. The mark was oblique in 509(88.68%) cases and impression corresponding to ligature material found in 126(21.95%) cases. Considering injury to neck structures most of them 448(78.04%) had stretching and elongation of neck, haemorrhage in underlying layers of neck skin in 372(64.81%). Injury to the other structures of neck were variable. Most of the victims 401(69.86%) hanged themselves at night. 545 body (94.95%) were recovered from inside the living room. Most victims had complete suspension 472 (82.23%).Conclusion : This retrospectivemedico legal study find out various data of hanging victims of one of the largest heath care center, Dhaka Medical College, which cover a large area of population. Though multi center prospective study should be carried out to find out our real situation.Northern International Medical College Journal Vol.7(1) Jul 2015: 110-114